Factors affecting denitrification in headwater prairie streams - Reisinger, Alexander Joseph (Kansas State University, 2010)
Human-induced stressors such as increased nitrogen (N) loadings, altered watershed land-use, and biodiversity losses are a few of the numerous threats to aquatic systems. Prairie streams experience natural disturbances, such as flooding and desiccation, which may alter responses to anthropogenic stressors. Denitrification, the dissimilatory reduction of NO3- to N gas (N2O or N2), is the only permanent form of N removal from terrestrial or aquatic ecosystems, and is important in mitigating N pollution to streams and downstream waters. Little is known about the relationships between denitrification and riparian prairie vegetation or large consumers. In the first chapter, I used outdoor mesocosms to determine the impact of a grazing minnow, Campostoma anomalum, on structural and functional responses of prairie streams to a simulated flood, focusing on denitrification. In terrestrial ecosystems, grazing can stimulate denitrification, but this has not been studied in streams. Ammonium (NH4+) enrichments, used to simulate fish excretion, alleviated N limitations on denitrification. Both fish and NH4+ affected algal biomass accrual, but only fish affected algal filament lengths and particulate organic matter. In a second experiment, I examined the impact of woody vegetation expansion, a primary threat to tallgrass prairie, on riparian and benthic denitrification. Expansion of woody vegetation in these grasslands is due primarily to altered fire regimes, which historically inhibited woody vegetation growth. To determine the effect of woody vegetation expansion on benthic and riparian denitrification, woody vegetation was removed from the riparian zone of a grazed and an ungrazed watershed. Both soil and benthic denitrification rates from this removal buffer were compared to rates in grassy or woody riparian zones. Riparian soil denitrification was highly seasonal, with greatest rates occurring during early spring, and rates being low throughout the remainder of the year. Benthic denitrification was also temporally variable but did not exhibit seasonal trends, suggesting benthic denitrification is driven by factors other than water temperature. Removal of woody vegetation stimulated soil and benthic denitrification rates over rates found in naturally vegetated riparian zones. Elevated N loadings will continue to affect aquatic ecosystems, and these effects may be exacerbated by biodiversity losses or changing riparian vegetation.
Keywords: Denitrification; Woody encroachment; Prairie streams; Nitrogen; Biodiversity; Ecosystem recovery; Biogeochemistry (0425); Biology, Ecology (0329); Biology, Limnology (0793)